Perceived severity and Barriers to Health Promotion of Male addicts in Early Recovery from Drug Use Disorder : Tingkat keparahan yang dirasakan dan Hambatan terhadap Promosi Kesehatan pada Pecandu Pria dalam Pemulihan Awal dari Gangguan Penggunaan Narkoba - Ali Mohammed Shkara; Hassan Ali Hussein (Academia Open, 2024)
Background: Drug addiction remains a significant public health issue globally, with substantial personal and societal impacts. Effective treatment and health promotion behaviors are crucial for recovery. Specific Background: In Iraq, the context of addiction treatment and the factors influencing health promotion behaviors among male addicts are underexplored. Knowledge Gap: There is limited understanding of the perceived severity and barriers to health promotion behaviors among male addicts in drug addiction centers in Iraq. Aims: Aims to assess the perceived severity and barriers to health promotion behavior among male addicts with a drug use disorder. Methods: A descriptive study design was utilized, with a convenience sample of 100 male individuals aged 15 to 45 from the Al-Ataa Hospital for Addiction and Psychological Rehabilitation. Data were collected via a questionnaire comprising socio-demographic characteristics and scales measuring beliefs regarding addiction. Cronbach's alpha for the perceived barriers and severity scales were 0.789 and 0.881, respectively. Results: The average participant age was 28 years, with 49% single, 71% living in lower-class neighborhoods, and 72% voluntary admissions. A significant relationship was found between educational level and health beliefs (p=0.00). The study revealed a high-level assessment of perceived severity and a moderate-level assessment of perceived barriers. Novelty: This study highlights the significant impact of educational level on health beliefs among male addicts, a relatively unexplored area in the region. Implications: The findings suggest that increasing awareness among patients and their families, establishing specialized hospitals, developing targeted policies, and leveraging media can enhance addiction treatment. This research underscores the need for comprehensive approaches involving various stakeholders to address drug addiction effectively. Highlights: High Perceived Severity: Addicts show high severity awareness. Education Impact: Significant link between education and health beliefs. Policy Recommendations: Establish specialized hospitals, targeted policies, media involvement. Keywords: drug addiction, health promotion, perceived barriers, perceived severity, Iraq